Towards a revision of Taraxacum sect. Borealia (Compositae, Crepidinae) in Siberia and the continental Far East, with special reference to the dandelions of the Altai and Kamchatka - Kirschner, Jan; Štěpánek, Jan; Buryy, Vladimir V. (Phytotaxa, 2025)
The genus Taraxacum (Asteraceae, Crepidinae) is rather underexplored in the Asiatic part of Russia, and many published names require a revision. This particularly concerns T. sect. Borealia, a circumpolar Arcto-Alpidic group. We revised all the published names referable to T. sect. Borealia from the continental Asiatic Russia. On the basis of our material from the Altai and Central Siberia, a new collection from Kamchatka and older herbarium collections, we recognize 62 species, including 20 new species, 13 from the Russian part of the Altai, four new species from Irkutsk Region, Siberia, and another two from Kamchatka. A rich cultivated collection from the Altai in Kazakhstan yielded another new species. With two exceptions, all the species are agamospermous, which was estimated on the basis of indirect indicators. Many of the previously published names are difficult to evaluate because of a scanty original material, imperfectly preserved type specimens, unknown achenes etc. The oldest name in T. sect. Borealia, T. ceratophorum (Ledeb.) DC., was frequently used in a very broad sense for the whole group of species. We examined the original material of Leontodon ceratophorus Ledeb. and compared it with other members of this section; we consider it as conspecific with T. trigonolobum Dahlst., and the name T. ceratophorum s. str. is therefore used for the latter taxon. A brief comparison of Taraxacum in northern Asia and the northernmost North America is provided; both floras share at least five dandelion species.